Design and operation of multivessel batch distillation - Anwaruddin, Hisyam (2012)
Distillation processes in chemical industries have shown significant roles for separating valuable compounds from a mixture. In a specific separation process like separation of perfumes, essential oils, and pharmaceutical products, batch distillation is somehow preferable than continuous one. Batch distillation, however, in these separation processes is advantageous, particularly in the flexibility of fluctuating concentration of feed and products, and in changing production capacity based on market demand. In addition, the separation can be performed in only single batch distillation column for all the changing conditions. Due to the dynamic behavior of the operation of batch distillation that leads to more difficult operation, such efforts have been done to attain the desired specifications and, at the same time, to increase the operability. The efforts include both the design and operation of batch distillation. This research focuses on the investigation of separation behavior of multivessel batch distillation for multicomponent mixtures. The distillation unit used in this research consists of two columns with a vessel between the columns, a reflux vessel on the top of the column, and a reboiler (still pot). The experimental data are validated by simulation. Several cases of separation processes are represented by case studies as follows: Top product recovery, removal of light and heavy impurities, and removal of middle boiling component. By using an ideal ternary mixture consisting of ethanol, 1-propanol, and n-butanol, the case studies were used to investigate the separation behavior. It is found that for the case of top product recovery, increasing the vessel holdup of the middle vessel did not make a significant effect to the increase of ethanol purity in top vessel. However, an increase of ethanol purity in top vessel was obtained by simultaneously increasing the middle vessel holdup and reducing the holdup of top vessel. In this case, reducing the top vessel holdup of 50% results in the maximum achievable ethanol purity in top vessel of 96%. For the case of removal of light and heavy impurities, the concern was on the trade-off between product purity and product recovery. An agreement was found to have 91% purity of 1-propanol in the middle vessel with recovery of 74%. However, if it is desired to produce high purity product with suffering on the product recovery, reprocessing the top and bottom product can be carried out to recover the middle component in another batch. In addition, for the case of removing a middle boiling component from a mixture, increasing the middle vessel holdup did not give significant effect to the ethanol purity in top vessel. This may, therefore, be uneconomical to carry out since it leads to more losses of ethanol in middle vessel. An additional investigation on an introduction of slop vessels in the operation of multivessel batch distillation was also discussed in this thesis through simulation works. For the case studies discussed, it is found that slop vessel holdup and slop vessel position simultaneously give significant effects on the product purity of respective vessels.